Is Nitrogen a Key Determinant of Water Transport and Photosynthesis in Higher Plants Upon Drought Stress? - Ding, Lei; Lu, Zhifeng; Gao, Limin; Guo, Shiwei; Shen, Qirong (Frontiers in Plant Science, 2018)
Drought stress is a major global issue limiting agricultural productivity. Plants respond to drought stress through a series of physiological, cellular, and molecular changes for survival. The regulation of water transport and photosynthesis play crucial roles in improving plants’ drought tolerance. Nitrogen (N, ammonium and nitrate) is an essential macronutrient for plants, and it can affect many aspects of plant growth and metabolic pathways, including water relations and photosynthesis. This review focuses on how drought stress affects water transport and photosynthesis, including the regulation of hydraulic conductance, aquaporin expression, and photosynthesis. It also discusses the cross talk between N, water transport, and drought stress in higher plants.